8.3k views
1 vote
Given ADC ACB and BDC BCA prove a squared + b squared = c squared. Use the two Column proof.

Given ADC ACB and BDC BCA prove a squared + b squared = c squared. Use the two Column-example-1
User Osi
by
5.5k points

1 Answer

5 votes

Answer:

a² + b² = c · (e + d) = c × c = c²

a² + b² = c²

Please see attachment

Explanation:

Statement, Reason

ΔADC ~ ΔACB, Given

AC/AD = BA/AC, The ratio of corresponding sides of similar triangles

b/e = c/b

b² = c·e

ΔBDC ~ ΔBCA, Given

BC/BA = BD/BC, The ratio of corresponding sides of similar triangles

a/c = d/a

a² = c·d

a² + b² = c·e + c·d

a² + b² = c · (e + d)

e + d = c, Addition of segment

a² + b² = c × c = c²

Therefore, a² + b² = c²

Given ADC ACB and BDC BCA prove a squared + b squared = c squared. Use the two Column-example-1
User Samuel Neugber
by
5.4k points